Practical Issues Related to Accounting for Employee Benefits in the Form of Shares or Stock Options - Marian SĂCĂRIN (CECCAR Business Review)

(untitled)
This article presents some of the practical issues related to the accounting of employee benefits in the form of equity instruments in accordance with IFRS 2 Share-based Payment. Some of the particularities presented can be used as reference by entities that do not apply International Financial Reporting Standards (IFRS), because the accounting regulations approved by Order of the Minister of Public Finance No. 1802/2014 are quite brief as regards the benefits granted to employees settled in equity instruments.